The Evolution of the Nurse’s Role in Domestic Hygiene – an Extended Historical Literature Review - Stone, Claire (2010)
The aim of this literature review is to examine the evolution of the nurse’s role. The specific focus is that of the traditional nursing role in domestic hygiene. The rationale for this responds to media criticism of modern hospital hygiene, where they suggest that that nurses should once again adopt domestic hygiene practices to tackle cross-infection. To discover the viability of this proposal, a review using methods of historiography will examine primary and secondary sources to provide a body of historical evidence concentrated over 60 years. A discussion on how the roles of nurses have changed since the start of the NHS in 1948 will take place. This is to establish what changes in nursing roles lead modern practices that do not include domestic hygiene. Methods of historiographical analysis were used to derive meaning from the sources and discussion. It was found that the history of nursing often repeats itself in terms of patterns of change and influence on nursing roles. The influential factors of political and social change, nursing education system alterations, advancements in medical sciences and professionalization of nursing were found to all be inter-linked. Over time, they have equally contributed to the movement of nursing roles away from domestic practices. The conclusion to this review found the media’s suggestions are not feasible. It is not possible for nurses to take on the domestic hygiene role in modern practice. Recommendations to combat negative press, that effects both the hospital and nursing in this matter, suggests that improved public education of the nurses role would promote better awareness and trust of the profession in terms of hygiene maintenance. Nurses are also recommended to improve their awareness of ward hygiene so they have the ability to recognise when they are exposed to inadequate standards, thus protecting their patients from infection.